Pengaruh Net Profit Margin Dan Total Asset Turnover Terhadap Return On Investment Pada Pt Jaya Real Property Tbk Periode 2014-2024 - Muhamad Arby Afdal; Muhamad Badru Zaman (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. This study aims to determine whether there is an influence between Net Profit Margin and Total Asset Turnover on Return On Investment at PT Jaya Real Property Tbk for the period 2014-2024, both partially and simultaneously. The method used is quantitative research. The data used is secondary data in the form of PT Jaya Real Property Tbk financial reports for the period 2014-2024. The data collection technique in this study uses classical assumption testing techniques, including normality testing, multicollinearity testing, heteroscedasticity testing, and autocorrelation testing. The data analysis technique in this study used multiple linear regression analysis processed using Eviews version 12. Based on the partial research results, Net Profit Margin has a significant effect on Return On Investment with a t-statistic value greater than the table t-value, namely 17,70049 > 2,26216 and a significance value of 0,0000 < 0,05. The Total Asset Turnover variable also has a significant effect on Return On Investment with a t-statistic value greater than the t-table, namely 38,74413 > 2,26216 and a significance value of 0,0000 < 0,05. Simultaneously, Net Profit Margin and Total Asset Turnover have a significant effect on Return On Investment with an F-statistic value greater than the F-table value, namely 947,3745 > 4,46 and a significance value of 0,0000 < 0,05.